Exploring the relationship between droughts and rural-to-urban mobility—a mixed methods approach for Pune, India - Karutz, Raphael; Kabisch, Sigrun (Frontiers in Climate, 2023)
Urbanization in the global South is intricately linked with the internal mobility of people and the impacts of climate change. In India, changing precipitation patterns pose pressure on rural livelihoods through the increasing frequency and severity of droughts, contributing to rural-to-urban mobility. At destination, however, insufficient information is available on the complex mobility backgrounds of the new arrivals. We employ a mixed-methods approach to investigate mobility patterns to Pune, India, with a special focus on the role of droughts. Combining a household survey with in-depth interviews and monthly precipitation data on district level, we use descriptive statistics and qualitative content analysis to show a significant relationship between drought at origin and mobility to Pune. Particularly affected are recent arrivals, migrants of rural origin and from other states, and those currently living in informal areas. The link between droughts and mobility decisions is usually indirect, hidden behind economic conditions such as the loss of agricultural jobs. Paradoxically, migrants affected by droughts at origin face increased flood risk at destination. This risk, however, is often consciously taken in favor of better livelihood opportunities and coping capacities. With climate scenarios projecting increasingly variable precipitation patterns, understanding the climate-mobility-urbanization nexus gains importance, especially for destination hotspots like the city of Pune.